Field reports, Iowa Bird Life, Lee Schoenewe - Schoenewe, Lee A.et al (1998)
An annotated list of birds sighted by Lee Schoenewe. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1998. Epson - sheet feed